UMKM Menuju Era Digital pada Kelompok Umik (Usaha Mikro) Di Desa Wori Kecamatan Wori Kabupaten Minahasa Utara: MSMEs Towards the Digital Era in the UMIK Group (Micro Enterprises) In Wori Village, Wori District, North Minahasa Regency - Tirayoh, Victorina Zusana; Latjandu, Lady, Rita Taroreh, Rita Taroreh (Vivabio: Jurnal Pengabdian Multidisiplin, 2023)
In the current digital era, people have been encouraged to choose methods that are fast, easy, and efficient; therefore, MSME business actors must also act more quickly and efficiently in order to be able to keep up with current developments and trends that are occurring in society. These changing circumstances and progress require business actors to adapt and switch to using digital platforms. Therefore, digitalization can be the right solution to adapt to maintain business and even develop business in the future.The object of this service activity is in Wori Village, Wori District, North Minahasa Regency, which has an entrepreneurial group that is classified as a micro enterprise (umik). Microbusinesses are productive businesses owned by individuals and/or individual business entities where the total assets owned are a maximum of IDR 50 million.The aim of this activity is to develop and build MSMEs, in this case the microbusiness group (umik) in Wori village, to become a business group that is "digitally literate" or utilises digital technology in running a business to increase income.The methods that will be used are lectures and counselling on strategies for building and developing a business, training on the use of internet technology or digitalization in business, and assistance to business actors in running a business by implementing internet technology as part of a business development strategy. The result of this programme is that the group of microbusiness actors (umik) in Wori village understand how to build and develop business strategies and use or utilise internet technology as part of the strategy to build and develop the business they are running. ABSTRAK Pada era digital saat ini, masyarakat telah terpacu untuk memilih metode yang serba cepat, mudah, dan efisien, oleh karena itu, para pelaku usaha UMKM juga harus bertindak lebih cepat dan efisien agar mampu menyeimbangi perkembangan zaman dan tren yang sedang terjadi di masyarakat. Perubahan keadaan dan kemajuan ini menuntut pelaku usaha untuk beradaptasi dan beralih menggunakan platform digital. Oleh karena itu, digitalisasi dapat menjadi sebagai solusi tepat untuk beradaptasi guna mempertahankan bisnis bahkan pengembangan bisnis di masa depan. Objek kegiatan pengabdian ini adalah di Desa Wori Kecamatan Wori Kabupaten Minahasa Utara yang memiliki kelompok wirausaha yang tergolong usaha mikro (umik). Usaha mikro adalah usaha produktif milik orang perorangan dan/atau badan usaha perorangan dimana total aset yang dimiliki maksimal sebesar Rp 50 juta. Tujuan kegiatan ini adalah bagaimana mengembangkan dan membangun UMKM dalam hal ini kelompok usaha mikro (umik) di desa Wori menjadi kelompok usaha yang “melek digital” atau memanfaatkan teknologi digital dalam menjalankan usaha untuk meningkatkan penghasilan. Metode yang akan dilakukan adalah Ceramah/penyuluhan tentang strategi membangun dan mengembangkan usaha, Pelatihan tentang penggunaan teknologi internet atau digitalisasi dalam usaha dan Pendampingan pelaku usaha dalam menjalankan usaha dengan menerapkan teknologi internet sebagai bagian dari strategi pengembangan usaha. Hasil dari program ini adalah kelompok pelaku usaha mikro (umik) di desa Wori memahami bagaimana strategi membangun dan mengembangkan usaha serta menggunakan/memanfaatkan teknologi internet sebagai bagian dari strategi membangun dan mengembangkan usaha yang dijalankan.